Development of Learning Media with Mathematical Understanding in Geometric Sequences and Series within Malay Islamic - Suci Amaliah; Syutaridho Syutaridho; Feli Ramury; Yuli Fitrianti (Jurnal Pendidikan Matematika, 2023)
This research aims to produce mathematical learning media for geometric sequences and series with the results of Malay Islamic acculturation which can be linked to mathematics as a valid, practical context and has the potential to influence mathematical understanding abilities. This research uses the Tessmer 1993 research procedure with two stages, namely introduction and prototyping with a formative evaluation flow. The research results show that learning media is suitable for use based on assessments. The validity of the media obtained from expert assessments is 93%, meaning the media is very suitable for use. The practicality of learning media obtained from the results of student use was 79%, meaning that the media was practically used. Regarding the potential influence on mathematical abilities in the media, the results obtained were 82%, meaning that learning media has the potential to influence mathematical understanding abilities obtained from the results of students' practice. The results of mathematical understanding ability were 75%, which means that the student's ability to understand geometric sequence and sequence material using the resulting learning media was good. In this way, the resulting learning media can be used in the learning process.